PELATIHAN PENJUALAN ONLINE UNTUK IBU-IBU PKK DI SAUNG SINGGAH TPU PONDOK KOPI, JAKARTA TIMUR - Melani Quintania; Resa Nurlaela Anwar; Ellena Nurfazria Handayani; Firsan Nova (UM Metro, 2020)
The purpose of this study is to provide training in the form of skills in building online-based businesses. In simple terms, the activity trains participants on how to market a product using the internet as the main capital. This online business training consists of three parts, namely providing material about business online, the direct practice of creating an account and using social media Instagram and marketplaces, and creating persuasive messages in order to attract buying interest. The results of this study are quite good. Housewives at Saung Singgah TPU Pondok Kopi, who participated in this training, we're able to understand the online business well, were able to create accounts on social media Instagram and the marketplace as a means of online sales quite well even though there were still mothers in making persuasive messages. -Mothers who have not been able to and have not been able to make good persuasive messages. It is hoped that the sustainability of this activity will provide deeper knowledge and insights about online-based businesses through social media and marketplaces.